The Concept of al-Ghāyah and Its Impact on the Jurisprudential Thought of the Companion Jābir ibn ‘Abd Allāh: An Applied Uṣūlī Study - Abdullah, Manal Obaid Hamad (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study explores the concept of ghayah (purpose or limit) as one of the foundational principles in Islamic legal theory (usul al-fiqh), which has been a point of contention among scholars due to its significant role in legal reasoning and the formulation of juristic rulings. Numerous jurisprudential issues have stemmed from this concept across various areas such as worship, transactions, personal status, and criminal law. Given its importance, this research aims to examine the meaning of ghayah, its classifications, and the scholarly debate regarding its evidentiary authority. The study also derives the legal principles of the Companion from his juristic branches, highlighting the practical applications of the concept of ghayah as reflected in the legal practice of the Companion Jabir ibn Abdullah.